Lens Thickness in Infants and Children with Cataracts - Libby Wei, MD; Taylor Kolosky; Sarah Byun; Alexandra S. Dolgetta, MD; Moran R. Levin, MD; Jana A. Friedman, MD; Monica M. Manrique, MD; Isabelle Dortonne, MD; Camilo Martinez, COA; Marlet Bazemore, MD; Mohamad S. Jaafar, MD; William P. Madigan, MD; et al. (Ophthalmology Science, 2025)
Purpose: The purpose of this study was to determine the association between lens thickness and cataract in participants aged 0 to 5 years. Design: This was a prospective, multicenter, case–control study. Participants: We enrolled 118 participants (171 eyes) aged 0 to 5 years, mean age 14.6 ± 17.0 months, range 0 to 60 months. Methods: Lens thickness was measured on 342 ultrasound biomicroscopy (UBM) images. Main Outcome Measures: Lens thickness; feasibility of lens thickness measurement from UBM images. Results: The mean lens thickness among noncataracts was 3.60 ± 0.17 mm, compared with 3.16 ± 0.61 mm among cataracts (P < 0.0001). Lens thickness <3.5 mm was significantly associated with increased odds of cataract; adjusted odds ratio = 5.99 (95% confidence interval, 2.41–14.88; P < 0.0003) among participants age 0 to 7 months. Lens thickness was significantly associated with cataract laterality among participants age 0 to 7 months (P < 0.0001). Conclusions: Quantitative UBM can be used to evaluate lens thickness in infants and children with congenital cataracts. The lens in congenital cataract eyes was thinner than that of controls among infants. Abnormal lens thickness was significantly associated with cataract. Future longitudinal studies will examine the association between lens thickness and postcataract surgery outcomes. Financial Disclosure(s): Proprietary or commercial disclosure may be found in the Footnotes and Disclosures at the end of this article.